The hotel industry in Singapore : an analytical framework - Chua, Benjamin Kah Wai (2015)
The hotel industry in Singapore is one of Singapore's pioneer service industries. Its contribution towards Singapore's transformation into today's cosmopolitan city-state cannot be understated. The industry's role in Singapore's modem economy continues to be as important as ever. Nevertheless, lacklustre performance of the industry, due to poor business planning and government policy oversights in the early and mid-Eighties, have given the industry a bad reputation among investors. On the first look, a casual observer may agree with the consensual view that the industry is a dog, unexciting and low growth. Whether that label is justified or not requires a deeper inspection and understanding of the facts and forces within and around the industry. The reader of the report will find that the biasness may be misplaced. It is granted that the industry cannot be considered a sunrise industry, but it is no sunset industry either. Lucrative opportunities await investors with a keen eye for bargains within this business, only if the investor knows where to look and what to look for. The reader will find a detailed discussion on the environment that hotels operate in, the macro forces as well as the industry tides that rock the industry incessantly.We believe that the discussion would provide most investors with a better understanding of the business and improve their chances in finding that elusive 'golden goose' hotel amongst a flock of ducks.